A novel scheme of binding update no sense drop BCE in LMA - Geaiger, Mohamed; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Elsheikh, Elsheikh Mohamed Ahmed (International Journal of Computer Science and Network Security (IJCSNS), 2014)
The frequent changes of Mobile Node (MN) location is going to increase rapidly as everything is a mobile presently. In order to achieve seamless mobility, mobility managements are considered as very important. The mobile IPv6 (MIPv6) is proposed and standardized by IETF. It is introduced to improve the host mobility management. But, it faces different problems when mobile nodes move between different network infrastructures. To overcome these issues, proxy mobile IPv6 PMIPv6 is introduced. PMIPv6 is a network based mobility management intended to improve handover delay by functioning mobility managements on behalf of mobile node. However, PMIPv6 added additional cost to the network by implementing mobile access gateway and bidirectional tunnel. Hence, network mobility NEMO standardized as extension to MIPV6 to support session continuity to the Internet services on behalf of mobile network nodes. But, still there are some issues such as packet loss and handover delay during the registration of MNNs and handoff of NEMO. The research in this area is very active, trying to solve these problems by integration of different mobility management’s schemes. In this paper, we investigate different integrations of mobility management’s schemes. This paper proposed a Binding Update No Sense Drop BCE in LMA BUNSD-LMA schema. The BUNSD-LMA aims to find possible solution to allow MNNs that are roaming in a PMIPv6 domain to perform seamless mobility whiles maintaining their session continuity through mobile router. In this scheme, we integrate PMIPv6 with NEMO BS and extend an existing binding update message format to register the prefix of MNNs in advance with short time. In addition to this, we considering the concept of investigated proposed schemas to enhance our solution.